2007
DOI: 10.1021/jo071030o
|View full text |Cite
|
Sign up to set email alerts
|

The First Example of a Diastereoselective Thio-Ugi Reaction:  A New Synthetic Approach to Chiral Imidazole Derivatives

Abstract: The first example of a diastereoselective thio-Ugi reaction with chiral alpha-methylbenzylamine is described. The reaction results in formation of two diastereomers of thioamides, the major of which was isolated. We have found that under similar conditions stereochemical results of the thio-Ugi reaction are opposite to stereochemical results of the Ugi reaction. Several chiral thioamides were synthesized. The reaction of thioamides with ammonia results in substituted amidines, which can be cyclized to imidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Not surprisingly, few successful examples of ammonia Ugi reactions are known. 1820 Thus, tritylamine as an ammonia surrogate was introduced in the Ugi MCR. 21 In this work, we wanted to perform the one-pot synthesis of tetrazolopiperidinones C using a suitable ammonia source in the Ugi tetrazole reaction and basic reaction conditions for postcyclization.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, few successful examples of ammonia Ugi reactions are known. 1820 Thus, tritylamine as an ammonia surrogate was introduced in the Ugi MCR. 21 In this work, we wanted to perform the one-pot synthesis of tetrazolopiperidinones C using a suitable ammonia source in the Ugi tetrazole reaction and basic reaction conditions for postcyclization.…”
Section: Resultsmentioning
confidence: 99%
“…There are many methods used for the synthesis of multisubstituted imidazoles. Some imidazoles have been prepared by Ugi reaction and Davidson cyclization or by reaction of imidazolium ylides and lithiated imidazoles . The multisubstituted imidazoles also synthesized by condensation of 1,2‐diketone or α‐hydroxy ketone with aldehyde and ammonium acetate on a solid support by microwave irradiation, by heterocyclic cope rearrangement, condensation of a 1,2‐diketone with an aryl nitrile and primary amine under microwave irradiation and N ‐alkylation of trisubstituted imidazoles .…”
Section: Methodsmentioning
confidence: 99%
“…151 As shown in Scheme 1.94, (S)-a-methylbenzylamine reacted with thiobenzoic acid, isobutyraldehyde, and an isocyanide to give the corresponding thioamide as a 2 : 1 mixture of two diastereomers from which the major (R)-product was separated by chromatography in 35% yield. Unexpectedly, the authors observed inversion of the stereoselectivity of the reaction upon replacement of thiobenzoic acid by benzoic acid, which furnished the corresponding (S)configured Ugi product as the major diastereomer in 80% yield and 55% de.…”
Section: Multicomponent Reactions Based On the Ugi Reactionmentioning
confidence: 99%